2007
DOI: 10.1097/sap.0b013e31802ec6b5
|View full text |Cite
|
Sign up to set email alerts
|

A New Method in the Treatment of Ear Amputation

Abstract: There have been plenty of reconstruction methods for ear amputation, and replantation preserves its importance. In situations where replantation is not feasible, various methods were proposed. We indicate an alternative technique for the ear amputation without replantation indication. The method of replacing of a vascular structure into the tunnel formed on the posterior side of the amputated ear was used instead of replacing the ear cartilage into a vascular area that was described in the literature of ear pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In 1972, Baudet et al 2 indicated that before adapting the amputated part to a vascular bed at the posterior auricular region, the excision of the posterior skin of the amputated ear and the opening of small windows over the cartilage could help in the composite nourishment of the ear. Alagöz et al 3 conducted a study on cartilage drilling in 2007.…”
mentioning
confidence: 99%
“…In 1972, Baudet et al 2 indicated that before adapting the amputated part to a vascular bed at the posterior auricular region, the excision of the posterior skin of the amputated ear and the opening of small windows over the cartilage could help in the composite nourishment of the ear. Alagöz et al 3 conducted a study on cartilage drilling in 2007.…”
mentioning
confidence: 99%
“…7 Many techniques described methods that suggested placing the auricular cartilage in a vascular area with staged transfers. 8 Another method is to cover the auricular cartilage with the grafted temporoparietal fascia flap. 1,9,10 The idea of our work is replacing the amputated ear cartilage with its pericondirum after deskinning to its original anatomic place and covering it with a vascular structure of temproparietal fascia, then with full-thickness graft removed from the amputated ear.…”
mentioning
confidence: 99%